The effectiveness of the drilling method on enriching students vocabulary: A Study at Seventh Grade of Islamic Junior High School An-Nuriyah Benjeng Gresik - Yuni Aliyatur Rofi'ah; Khoirul Huda (JEET, Journal of English Education and Technology, 2020)
This study is generally attempted to find the effectiveness of the drill method on student’s vocabulary skill for the first-grade student’s at MTs. An-Nuriyah Benjeng Gresik academic year 2016/2017. To know this technique is valid or not, the researcher used a pre-experimental study applied in VII A class. The research has been done in six meetings that are designed, First meeting is for pre-test, four sessions are for treatments, and the last session is for post-test. As the quantitative method, the researcher analysed the data by using t-test. The result shows that Three is a significant difference in the student’s vocabulary achievement taught with drill method. The researcher uses the degree of significance of 5% and 1%. In the table of relevance, it can be seen the df 24 and the degree of importance of 5% and 1% the value of the degree of significance are 2,06 and 2,80. If compare with each value of the degrees of relevance, the result is 2,06< 10,506 > 2,80. The result of calculation t0 (t-observation) is higher than tt (t-table), t0>tt, the null hypothesis (H0) is rejected. If the result of calculation t0 (t-observation) is lower than tt (t-table), t0<tt, the null hypothesis is accepted. Since the score obtained from the result of calculating, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. In other words, the writer hypothesis is accepted. It means that there are significant differences between a student’s achievement in learning vocabulary skill using the drill method.